From Touch to Talk: Transforming Mobile Interactions with Voice-based Artificial Intelligence - Mittal, Mehak; Manocha, Sanjay (International Journal of Interactive Mobile Technologies (iJIM), 2025)
The rapid evolution of mobile technology has commenced in a new era of interaction paradigms, with “voice-based artificial intelligence (VAI)” emerging as a major disruptive influential force in user engagement. This study explores the factors that influence the adoption of voice-based AI on smartphones among Indian consumers. Using a quantitative research design, data were gathered from 500 Indian mobile users who have prior experience with voice assistants. The study is based on constructs from the “technology acceptance model (TAM)” and related theories to examine the influence of “Perceived Usefulness”, “Perceived Ease of Use”, “Perceived Enjoyment”, “Social Influence”, “Trust”, and “Perceived Privacy Risk” on “Attitude to Use” and “Actual Usage of voice-based AI”. To determine the measurement and structural aspects of the model, the dataset was tested using “Partial Least Squares Structural Equation Modelling (PLS-SEM)”. Based on the findings, “Perceived Usefulness”, “Perceived Ease of Use”, “Perceived Enjoyment”, and “Trust”, and “Social Influence” positively influence users’ “Attitude to Use”, which has a positive effect on “Actual Usage”. “Perceived Privacy Risk” negatively affected Attitude to Use. This study enhances the existing literature by focusing on the primary reasons for adoption in India. The results provide marketers and developers with insightful information. It implies that stakeholders may promote wider adoption and use of voice-based AI technology by building confidence, improving user experience, and resolving privacy concerns.